The 2013 Educational Reform in Mexico and its effects on teacher’s work precariousness - Silva Montes, Cesar; Gutiérrez Lozano, Arturo (Education Policy Analysis Archives, 2020)
This article analyzes the increase in the precariousness of Mexican public education since the approval and implementation of the Educational Reform in 2013. The basis of the study is the analysis of the discourse of public basic education teachers in Ciudad Juarez regarding the loss of earned labor rights. For example, the inability of new teachers to receive the same salaries and benefits as the previous generation of teachers, as well as the increase in responsibilities, activities, and obligations. In addition, teaching flexibilization allows teachers to recognize working conditions as precarious, compared to previous jobs, they conceive it as stable employment. This research shows how managerialism, Toyotism, flexibilization and outsourcing models according to the international neoliberal trend eliminates the union identity of the teaching profession and reconfigures it on the basis of the logic of efficiency and effectiveness through standardized and decontextualized evaluations, as a recent phenomenon in the Mexican teaching profession.